2012
DOI: 10.1364/oe.20.017029
|View full text |Cite
|
Sign up to set email alerts
|

Integrated photonic building blocks for next-generation astronomical instrumentation I: the multimode waveguide

Abstract: Abstract:We report on the fabrication and characterization of composite multimode waveguide structures that consist of a stack of single-mode waveguides fabricated by ultrafast laser inscription. We explore 2 types of composite structures; those that consist of overlapping single-mode waveguides which offer the maximum effective index contrast and non-overlapped structures which support multiple modes via strong evanescent coupling. We demonstrate that both types of waveguides have negligible propagation losse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Thomson et al was the first to demonstrate a laser-inscribed photonic lantern with 16 ports [6], as shown in Figure 7. Laser inscription requires careful optimisation of the multi-mode section of the lantern in order to achieve low losses [119]. With optimised design of the length as well as the shape of the tapered transition, a multi-mode to slit reformatting integrated photonic lantern can achieve 95% efficiency at a wavelength of 1550 nm excluding the glass absorption losses [120].…”
Section: Integrated Photonic Lanternsmentioning
confidence: 99%
“…Thomson et al was the first to demonstrate a laser-inscribed photonic lantern with 16 ports [6], as shown in Figure 7. Laser inscription requires careful optimisation of the multi-mode section of the lantern in order to achieve low losses [119]. With optimised design of the length as well as the shape of the tapered transition, a multi-mode to slit reformatting integrated photonic lantern can achieve 95% efficiency at a wavelength of 1550 nm excluding the glass absorption losses [120].…”
Section: Integrated Photonic Lanternsmentioning
confidence: 99%
“…The bend losses were isolated by removing the affects of coupling and bulk material absorption losses. Loss due to the coupling of light into and out of the chip was determined to be 9 ± 2%, with absorption loss in the Eagle2000 glass at 1550 nm also accounted for ( = 0.0075 ± 0.0003 mm -1 ) [23]. Although the series of guides had varying lengths, the bend losses were rescaled to a waveguide length of 30 mm for comparative purposes.…”
Section: Curvature and Power Lossmentioning
confidence: 99%
“…So far in published results, photonic lantern core geometries have consisted of hexagonal lattices, rounded array or square lattices with the number of cores approximately equal to the number of final waveguide modes as required [12,13,[17][18][19]. However, it has been theoretically demonstrated that the best starting point for a low loss lantern design is an uncoupled core geometry that best approximates or samples the geometry of the modes of the final MM fiber [14,20,21].…”
Section: Optimum Waveguide Geometrymentioning
confidence: 99%
“…In this case, the isolated singlemode waveguide cores are created and gradually brought together such as they couple strongly. This creates the adiabatic optical transition required for the single-mode to multimode conversion, and the strongly coupled cores form the final multimode composite waveguide [18,19,23]. ULI photonic lanterns, also called integrated photonic lanterns, are a very versatile approach.…”
Section: Different Approachesmentioning
confidence: 99%